2014
DOI: 10.1093/bja/aet348
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effects of albumin 5%, hydroxyethyl starch 130/0.4 6%, and Ringer’s lactate on blood loss and coagulation after cardiac surgery

Abstract: Despite equal blood loss from chest drains, both colloids interfered with blood coagulation and produced greater haemodilution, which was associated with more transfusion of blood products compared with crystalloid use only.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
85
1
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(99 citation statements)
references
References 42 publications
(31 reference statements)
10
85
1
3
Order By: Relevance
“…A large observational study with over 6000 patients found increased need for RRT among patients undergoing cardiac surgery who received either HES or gelatin compared to crystalloids [29]. HES increased the need for RRT and blood products during cardiac surgery [30]. Triggered by safety concerns from large-scale RCTs, the European Medicines Agency (EMA) re-assessed the safety and efficacy of HES solutions and decided to restrict its use in critically ill patients.…”
Section: Discussionmentioning
confidence: 99%
“…A large observational study with over 6000 patients found increased need for RRT among patients undergoing cardiac surgery who received either HES or gelatin compared to crystalloids [29]. HES increased the need for RRT and blood products during cardiac surgery [30]. Triggered by safety concerns from large-scale RCTs, the European Medicines Agency (EMA) re-assessed the safety and efficacy of HES solutions and decided to restrict its use in critically ill patients.…”
Section: Discussionmentioning
confidence: 99%
“…The colloids impaired clot formation and clot strength more than Ringer's lactate and the amount of transfused blood products was larger in the patient groups receiving colloids than Ringer's lactate [17].…”
Section: Discussionmentioning
confidence: 81%
“…The mean estimated blood loss was 773 ± 287 mL. We assumed that half of the standard deviation (143 mL) would be considered a clinically significant difference in blood loss between the HES group and the crystalloid group as previously described elsewhere [15]. Furthermore, 143 mL is approximately 20 % blood reduction, which is a clinically meaningful.…”
Section: Methodsmentioning
confidence: 99%